Depression and Its Contributing Factors: A study among staff of an academic institution in Malaysia - Razali, Salmi; Yung-An, Chua; Mat Nazali, Mohd Izwan; M Nawawi, Hapizah (Environment-Behaviour Proceedings Journal, 2019)
Information on depression and its contributing factors among the staff of the academic institution is sparse. Hence, this study aimed to determine the prevalence of depression among them and investigate its contributing factors. We used the Depression, Anxiety and Stress Scale 21-item and pro forma questionnaires to assess the presence of depression, sociodemographic factors, personal factors and job-related factors. Of 278 participants, 27.7% had clinical depression. Contributing factors include inadequate workplace facilities, low-tier job category, working in urban campus and low income. Addressing factors underpin depression among staff in the academic institution is crucial to ensure early interventions can be offered. Keywords: Depression; Academic Institution; Workers; Contributing Factors eISSN: 2398-4287 © 2019. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open access article under the CC BYNC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peer–review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. DOI: https://doi.org/10.21834/e-bpj.v4i12.1894